Given the equation of the circle:
![x^2+4x+y^2-12y=-24](https://img.qammunity.org/2023/formulas/mathematics/college/ln7ierlpri6he53mvnbmfv8mg2xb3ylvwk.png)
We will complete the squares for x and y to write the equation of the circle as:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/5s77z5lwu6jnvb5vkwanu2jvhq5sh1qkc3.png)
Where (h,k) is the coordinates of the circle and r is the radius of the circle
so, the equation will be:
![\begin{gathered} (x^2+4x+4)+(y^2-12y+36)=-24+4+36 \\ \\ (x+2)^2+(y-6)^2=16 \\ \\ (x+2)^2+(y-6)^2=4^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7trgvz4hal855118udmejhhhh4y7re01tm.png)
So, the radius of the circle = 4
And the center of the circle = ( -2, 6 )
Now, we will make the transformation for the circle:
Shift 1 unit up, the center will be = ( -2, 7 )
shift 2 units right, the center will be = ( 0, 7 )
Reflection across the x-axis, the center will be = ( 0, -7)
So, the equation of the circle after transformation will be:
![(x-0)^2+(y+7)^2=4^2](https://img.qammunity.org/2023/formulas/mathematics/college/jbyh7qzaicfv6a3lx6ytesubh0q3nybqsb.png)
So, the answer will be:
![(x-0)^2+(y+7)^2=16](https://img.qammunity.org/2023/formulas/mathematics/college/u9egmd3u9q0nmxrg6qglzn76lw2dtu76pq.png)